You are on page 1of 10

Objective: *Use the substitution method to solve a system of linear equations in two variables.

Substitution is when you replace one thing with another thing. Substitution is ideal to use if one of the variables has already been isolated in the original system of equations.

Steps: 1. Pick an equation (thats easiest to get one of the variables by itself) and solve for a variable. 2. Substitute into the OTHER equation. 3. Solve for the first variable. 4. Substitute and solve for the second variable (doesnt matter which equation). 5. Check your solution (YES, you need to check your answer!)

x + y = 56 (1)

From (2) substitute y = 7x + 8 into eq(1).

y = 7x + 8 (2)
x + 7x + 8 = 56 8x + 8 = 56 8x = 48 x=6 Check solution x = 6 and y = 50 in equation (2) y = 7x + 8 50 = 7(6) + 8 50 = 42 + 8 50 = 50 LS = RS Since LS = RS, solution set: (6,50)

Substitute x = 6 into eq(1)


x + y = 56 6 + y = 56 y = 50

3x y = 26

(1)

4x + 5y = 3
(1) 3x y = 26

(2)

Since no variables are isolated, we need to isolate one before we can substitute. Substitute into y = 3x 26 into (2).

-y = -3x + 26
y = 3x 26

4x + 5y = 3 4x + 5(-26 + 3x) = 3 4x 130 +15x = 3 19x 130 = 3 19x = 133 x=7

3x y = 26

(1)

4x + 5y = 3

(2)

Check solution x = 7 and y = -5 into (2) 4(7) + 5(-5) = 3 28 25 = 3 3=3 LS = RS Therefore, since LS = RS the solution set = (7,-5)

Substitute x = 7 into (1).


3x y = 26 3(7) y = 26

21 y = 26 y=5
y = -5

Solve the system of equation by substitution. Substitute the expression in the second equation into the first equation and solve.

3x 2y = -2 (1)
x = -y + 6 (2)

From (2) substitute x = -y + 6 into eq(1).

Substitute y = 4 into eq(2) 3(-y + 6) 2y = -2 x = -y + 6 -3y 18 2y = -2 x=2 x = -4 + 6 -5y = -2 - 18 -5y = -20 Check solution x = 2 & y = 50 in equation (2) 3x 2y = -2 y=4 -2 = -2 3(2) 2(4) = -2 LS = RS 6 - 8 = -2 solution set: (2,4)

-3x 9y = 7 (1) x + 3y = 12 (2)

Rewrite (2) in terms of x x = -3y + 12 (3) From (3) substitute x = -3y + 12 into eq(1).

-3(-3y + 12) 9y = 7 9y 36 9y = 7 0y = 7 + 36 0 = 43

LS RS, False! No Solution Lines are parallel

Solve the system of equation by substitution. Substitute the expression in the second equation into the first equation and solve.

-4x + 4y = -8 (1)
y=x-2 (2)

From (2) substitute y = x 2 into eq(1).

-4x + 4(x-2) = -8 -4x + 4x - 8 = -8 -4x + 4x = -8 + 8 0=0

LS = RS Infinite solutions

The 2 lines coincide

Problem Set 3.8 (TB pp. 213-214)


Individual Practice: Homework Even numbers Nos. 2, 4, 6,48